Nursing diagnosis and sociodemographic factors in people living with HIV (Research, Society and Development, 2022)
Objective: to identify the most frequent nursing diagnoses and their relationship with sociodemographic factors among PLHIV. Method: prospective study with a quantitative approach. Data collection was carried out from July 2020 to March 2021, at the immunology clinic in Rio de Janeiro. The instrument was based on the Wanda Horta theory; cross-mapping was performed and the content validation index was calculated. Results: 40 interviews were carried out, totaling 21 nursing diagnoses. Of these, the most prevalent were the diagnoses of “risk of compromised human dignity”, “willingness to self-management of improved health”, “insomnia” and “risk of loneliness”. Conclusion: in the present study, the most evident nursing diagnoses were those involving psychosocial needs that address stigmatization, discrimination, dysfunctional family support, anxiety and coping with the disease. Emphasizing that society's prejudice towards PLHIV is an important factor, being more emphasized in this research.